Callogenesis and organogenesis of Lavandula vera DC. - M Peyvandi; L Kazemi; A Majd (فیزیولوژی محیطی گیاهی, 2009)
Lavender (Lavandula vera DC) is an important ornamental and aromatic plant. In vitro culture through callogenesis is proposed to be an alternative for vegetative propagation. The effects of different cytokinins were investigated on callogenesis and organogenesis of Lavandula vera. Nodal explants were cultured in the MS medium supplemented with different concentrations of cytokinins (benzyl amino purine (BAP), Kinetine (Kin) solely or in combination with each other. Ten days after culturing, callogenesis was observed. After 3 weeks some granular shapes were appeared on the calli which formed sprouts or roots. Calli which were grown in the medium with 2iP (1-2 mg/l) or BAP (1-2 mg/l) produced shoots. The maximum number of shoots was achieved in the medium supplemented with BAP (2 mg/l). The production of shoots and roots were occurred at the same time. The maximum level of root formation was gained in the medium with BAP (1 mg/l). Forty five old days calli were subcultured in the same culture media. Shoot formation was achieved in the media supplemented with 2iP (1-2 mg/l) or BAP (1-2 mg/l) and combination of BAP and Kin (1mg/l). In the subculture media root formation was not occurred.